Promotion activities of wood industry in Slovenia and in Croatia - Marko Dušak (Slovenian Forestry Institute, 2016)
Wood industry is among the most important industrial sectors in Slovenia and Croatia. In both countries, wood sector is a part of the national strategy plans and one of the industrial branches considered national economy boosters. But media coverage of wood industry and furniture manufacturing in Slovenia, as well as in Croatia, is far behind the promotion enjoyed by other industrial branches. This paper will give the current situation in promotional activities of wood sector in Slovenian and Croatian media and demonstrate the existing differences among given countries. Also, it will present some ideas on improving this situation according to media share of other highly profiled industrial branches in some southeastern European countries.